Value Perception as Mediating between Service Quality and Customer Satisfaction in Café’s Customer - Alifah, Anis; Fajri, Annisa (Economics and Business International Conference Proceeding, 2024)
Study This aim For analyze influence quality service to satisfaction customers mediated by perception​ value at Café Luggo Outlet Tembalang. Subjects in research This is ever customer​ buy products at Café Luggo Outlet Tembalang at least more from three times. Retrieval technique sample use probability sampling technique with purposive sampling method. In research This sample A total of 100 respondents were taken from spread questionnaire. Analytical tools used​ is Smart Partial Least Square (SmartPLS 4.0). Based on analysis that has been done done obtained results that quality service influential positive and significant to satisfaction customers, quality service influential positive and significant to perception value, perception mark have influence to satisfaction customer, perception mark have influence positive and significant in mediate connection quality service to satisfaction customer.